ANALISIS PERILAKU GAYA HIDUP SEHAT PARTISIPAN OLAHRAGA DI HALAMAN KANTOR GUBERNUR PROVINSI JAMBI - Alif Nofitra Firly; Ilham; Putra, Angrawan; Hendri Munar; Sugih Suhartini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe healthy lifestyle behavior in people who participate in sports activities in the Jambi Provincial Governor's Office Yard. This research is motivated by the increasing interest of the public in carrying out sports activities in public spaces as one of the efforts to maintain health. However, there is no clear information on how the healthy lifestyle of sports participants is, especially related to eating and drinking, personal hygiene, environmental cleanliness, disease prevention, and the balance between activities, rest, and exercise. The method used in this study is a quantitative descriptive method. The research sample amounted to 100 sports participants who were active in the Jambi Provincial Governor's Office and were selected using random sampling techniques. Data collection was carried out through the distribution of questionnaires containing five indicators of healthy living behavior, namely behavior towards food and drinks, personal hygiene, environmental cleanliness, behavior towards illness and disease, as well as balance of activities, rest, and exercise. The data obtained was then analyzed using descriptive statistical techniques in the form of percentages. The results of the study showed that the healthy lifestyle behavior of sports participants in the Jambi Provincial Governor's Office was generally in the high category. A total of 42 respondents (42.00%) were included in the very high category, 37 respondents (37.00%) in the high category, 16 respondents (16.00%) in the medium category, and 5 respondents (5.00%) in the low category. None of the respondents were in the very low category. The findings indicate that most exercise participants have implemented healthy living behaviors well in their daily lives. However, increasing awareness and consistency in implementing all aspects of a healthy lifestyle still needs to be done to support a more optimal quality of health.